Composites and Their Applications - Hu, Ning (IntechOpen, 2012)
Composites are a class of material, which receives much attention not only because it is on the cutting edge of active material research fields due to appearance of many new types of composites, e.g., nanocomposites and bio-medical composites, but also because there are a great deal of promise for its potential applications in various industries ranging from aerospace to construction due to its various outstanding properties. This book mainly describes some potential applications and the related properties of various composites by focusing on the following several topics: health or integrity monitoring techniques of composites structures, bio-medical composites and their applications in dental or tissue materials, natural fiber or mineral filler reinforced composites and their property characterization, catalysts composites and their applications, and some other potential applications of fibers or composites as sensors, etc. This book has been divided into five sections to cover the above contents.